Testing the efficacy of different substances against Arion slugs (Arionidae) under laboratory conditions - Žiga LAZNIK; Maja MIHIČINAC; Jaka RUPNIK; Matej VIDRIH; Igor PRŠA; Stanislav TRDAN (Acta Agriculturae Slovenica)
In 2008 and 2009 we studied molluscicidal activity of 26 substances in 89 different treatments under laboratory conditions. The experiments in which slugs (Arion spp.) were a part took place in two series: 1) with the injection of active substances in slug intestines; and 2) with the application of pellets. After giving the injection we observed 100% mortality of slugs in treatments with Bacillus thuringiensis var. kurstaki (0.25 ml in 10% concentration/individual), caffeine (0.25 ml in 10% concentration/individual), sodium dodecyl sulphate (0.25 ml in 10% concentration/individual, 0.125 ml in 10% concentration/individual, 0.125 ml in 5% concentration/individual, 0.0625 ml in 10% concentration/individual), and pirimicarb (0.25 ml in 10% concentration/individual, 0.125 ml in 10% concentration/individual, 0.125 ml in 5% concentration/individual, 0.0625 ml in 10% concentration/individual). Meanwhile, the application of pellets resulted in the highest (100%) slug mortality when sodium dodecyl sulphate in 0.5% concentration with caraway as a supplement was used.